Effects of credit risks on growth of commercial banks in Nepal - Humagain, Anil (Journal of Management and Development Studies, 2023)
This study aims to investigate the effects of credit risk management tools on the growth of commercial banks in Nepal. The study utilized a descriptive research design with quantitative research methods. The data were collected from System-X, for a period of 12 years from 2011 to 2022. The results of the study indicate that non-performing loans (NPLs) have a significant negative effect on bank performance and growth of total assets in Nepal. The average non-performing loans of the commercial banks during the study period was 1.5 percent. During this period, the average total assets growth of the banking sector was 19.94 percent. Credit to Deposit Ratio, Non-Performing Loan, and Inflation were statistically significant to predict the growth of commercial banks. The study also revealed that credit management practices among Nepalese commercial banks are suboptimal. This study further suggests that the regulatory authority should periodically review the credit risk management tools employed by banks in order to mitigate the credit risks.